The Use of Artificial Intelligence in Enhancing Students’ Ability to Understand Learning Materials at SMA Negeri 1 Tual - Ahmad Rahanyaan; Rosdiana Rahantan (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
Artificial Intelligence (AI) is a field of human knowledge that is currently developing very rapidly, especially in the digital era. Artificial Intelligence technology represents one of the most revolutionary innovations in the development of education worldwide. The use of AI-based technology in the education sector in Indonesia is still relatively new and inevitably faces various challenges; not all schools, particularly those in regional areas, have implemented AI technology in learning, either by teachers or students, to support independent learning and enhance the teaching and learning process. This study aims to examine how Artificial Intelligence (AI) is used by students to improve their ability to understand learning materials and to identify the impact of AI usage on students at SMA Negeri 1 Tual. The study employs a mixed-methods approach, combining quantitative and qualitative methods. Data were collected through questionnaires measured using a Likert Scale and analyzed using descriptive statistics, while interview data were collected to describe the benefits and impacts of AI usage. The results show that 100% of students use AI, and 61% of respondents agree that the use of Artificial Intelligence significantly helps improve their ability to understand learning materials. The positive impacts of AI utilization include serving as a tool to quickly and comprehensively find answers to assignments perceived as difficult. In addition, AI contributes to helping students independently enhance critical thinking and creativity, as well as enabling easy, practical, and flexible access to information anytime and anywhere. However, there are also negative impacts, as frequent and intensive use of AI technology over a long period has the potential to create dependency on AI applications, reduce social interaction among classmates, and potentially decrease critical thinking skills. This study is expected to provide input for the education sector in integrating AI applications into school curricula and to encourage students to use AI technology more wisely.